Vision status and reading test results in Norwegian adolescents - Hagen, Lene; Gilson, Stuart J.; Baraas, Rigmor C. (Scandinavian Journal of Optometry and Visual Science, 2020)
Uncorrected vision anomalies may cause headaches and may affect reading and academic performance. The purpose of this study was to quantify the frequency of vision anomalies, frequency of eye examinations, and use of corrective eye wear in adolescents in Norway, and to explore whether such vision anomalies affect reading test results or frequency of headaches. A cross-sectional study was performed in 436 adolescents (42.0% males) aged 16–19 years living in South-East Norway. Cycloplegic autorefraction, habitual stereoacuity, and habitual monocular amplitudes of accommodation were measured, and all participants reported the frequency of eye examinations, the use of spectacles and/or contact lens wear, and the frequency of headaches. Reading comprehension and decoding skills were evaluated for a subgroup of the participants (189 participants, 34.4% males) by their performance in national reading tests. Vision anomalies were defined as having refractive errors, poor habitual stereoacuity, or poor habitual amplitude of accommodation in at least one eye. Overall, 44.0% were classified as having a refractive error, and a total of 61.9% were measured to have vision anomalies. More frequent headaches were associated with poor habitual amplitude of accommodation when adjusted for sex (p = 0.04). The frequency of poor reading comprehension was higher in the group of adolescents with vision anomalies (n = 109, 31.2%) compared with those with no vision anomalies (n = 80, 18.8%; p = 0.05). Of those with vision anomalies, 33.5% had never had an eye examination, and 63.9% reported not wearing a correction. In Norway, there is no mandatory vision screening after 4 years of age. The results here show that a nation-wide programme of regular eye examinations and proper treatment of vision anomalies for all children and adolescents in Norway should be considered. Identifying and treating children with common eye problems in primary and secondary school will improve educational attainment and increase each child’s chances of succeeding in further education.